FORMULATION OF EYESHADOW CREAM COMBINATION OF EXTRACT SPISSUM BUTTERFLY PEA FLOWER (Clitoria ternatea L.) WITH SECANG WOOD (Caesalpinia sappan L.) AS A NATURAL COLOR - Dini Agustina Yuniaty; Deni Rahmat; Rahmaniar Rachmat (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Eye shadow is one of the decorative cosmetic that contains color that is applied to the eyelids. Eye shadows were generally blue, pink, dark red, silver, green, and brown. Natural dyes are derived from plants, animals, and microorganisms. Butterfly pea flower (Clitoria ternatea L.) and secang wood (Caesalpinia sappan L.) are plants that contain natural dyes that can be used as dyes. The two plants were removed by maceration in 70% ethanol. Eye shadow preparation using a combination of extract spissum of Â butterfly pea flower and secang wood produces eye shadow with a purple color in 3 formulations, namely F3 extract spissum butterfly pea flower and secang wood (3:2), F4 extract spissum butterfly pea flower and secang wood (2:3), F5 extract spissum butterfly pea flower and secang wood (1:4). In the hedonic test, there was no significant difference >0.05% among F3, F4, and F5. Thus, the results of the irritation test showed that the eye shadow cream preparation produced an irritation index of 1.00, namely, mild irritation. Keywords: Eye shadow, butterfly pea flower, Secang wood.